Drivers of plankton community structure in intermittent and continuous coastal upwelling systems–from microbes and microscale in-situ imaging to large scale patterns - Schmid, Moritz S.; Sponaugle, Su; Thompson, Anne W.; Sutherland, Kelly R.; Cowen, Robert K. (Frontiers in Marine Science, 2023)
Eastern Boundary Systems support major fisheries whose early life stages depend on upwelling production. Upwelling can be highly variable at the regional scale, with substantial repercussions for new productivity and microbial loop activity. Studies that integrate the classic trophic web based on new production with the microbial loop are rare due to the range in body forms and sizes of the taxa. Underwater imaging can overcome this limitation, and with machine learning, enables fine resolution studies spanning large spatial scales. We used the In-situ Ichthyoplankton Imaging System (ISIIS) to investigate the drivers of plankton community structure in the northern California Current, sampled along the Newport Hydrographic (NH) and Trinidad Head (TR) lines, in OR and CA, respectively. The non-invasive imaging of particles and plankton over 1644km in the winters and summers of 2018 and 2019 yielded 1.194 billion classified plankton images. Combining nutrient analysis, flow cytometry, and 16S rRNA gene sequencing of the microbial community with mesoplankton underwater imaging enabled us to study taxa from 0.2µm to 15cm, including prokaryotes, copepods, ichthyoplankton, and gelatinous forms. To assess community structure, >2000 single-taxon distribution profiles were analyzed using high resolution spatial correlations. Co-occurrences on the NH line were consistently significantly higher off-shelf while those at TR were highest on-shelf. Random Forests models identified the concentrations of microbial loop associated taxa such as protists, Oithona copepods, and appendicularians as important drivers of co-occurrences at NH line, while at TR, cumulative upwelling and chlorophyll a were of the highest importance. Our results indicate that the microbial loop is driving plankton community structure in intermittent upwelling systems such as the NH line and supports temporal stability, and further, that taxa such as protists, Oithona copepods, and appendicularians connect a diverse and functionally redundant microbial community to stable plankton community structure. Where upwelling is more continuous such as at TR, primary production may dominate patterns of community structure, obscuring the underlying role of the microbial loop. Future changes in upwelling strength are likely to disproportionately affect plankton community structure in continuous upwelling regions, while high microbial loop activity enhances community structure resilience.